Update on the prevention of death from ruptured abdominal aortic aneurysm. (September 2017) - Jacomelli, Jo; Summers, Lisa; Stevenson, Anne; Lees, Tim; Earnshaw, Jonothan J
Objectives: To monitor the early effect of a national population screening programme for abdominal aortic aneurysm in 65-year-old men. Setting: The study used national statistics for death rates from abdominal aortic aneurysm (Office of National Statistics) and hospital admission data in England (Hospital Episode Statistics). Methods: Information concerning deaths from abdominal aortic aneurysm (ruptured and non-ruptured) (1999–2014) and hospital admissions for ruptured abdominal aortic aneurysm (2000–2015) was examined. Results: The absolute number of deaths from abdominal aortic aneurysm in men and women aged 65 and over has decreased by around 30% from 2001 to 2014, but as the population has increased, the relative reduction was 45.6% and 40.0%, respectively. Some 65% of all abdominal aortic aneurysm deaths are in men aged over 65; women aged 65 and over account for around 31%. Deaths from ruptured abdominal aortic aneurysm in men aged 60–74 (the screened group) appear to be declining at the same rate as in men aged 75 and over. The relative decline in admissions to hospital with ruptured abdominal aortic aneurysm may be greater in men and women aged 60–74 (which contains the screened group of men), than those older, giving the first possible evidence that abdominal aortic aneurysm screening is having an effect. Conclusion: The death rate from abdominal aortic aneurysm is declining rapidly in England. There is the first evidence that screening may be contributing to this reduction.